Strategi Bank Syariah Indonesia KCP Tulungagung Trade Center dalam Menghadapi Persaingan di Industri Perbankan - Rossa Silviany; Muhammad Alhada Fuadilah Habib (Journal on Education, 2023)
The purpose of this study was to find out the strategy implemented by BSI KCP Tulungagung in winning the banking industry market amidst the many other banking industries around it based on the theory put forward by Treacy and Wiersema namely Value Discipline with three main points including: Operational Excellence, Customer Intimacy, and Product Leadership . The method used in this study is a qualitative descriptive analysis approach with data sources obtained from observation, interviews and documentation. In-depth interviews were conducted with informants from BSI KCP Tulungagung Trade Center employees including leaders, customer service and customer business staff, and 3 customers. In addition, this research is also supported by secondary data sources from journals, previous studies, and BSI's 2021 Annual Financial Report. The results show that the value discipline strategy implemented by the BSI KCP Tulungagung Trade Center includes Operational Excellence including broadcasting products from savings to Funding according to customer needs, reliable service by providing the best solutions to customers' financial problems, and competitive prices with a margin of 2.22% and profit sharing of up to 25%, and avoiding problems with customers because they provide services according to SOP. Second, Product Leadership includes offering products with cross selling and always innovating to suit market needs. Third is Customer Intimacy. This strategy includes two types, namely tangible and intangible which are implemented in order to establish close relationships with customers. BSI KCP Tulungagung Trade Center focuses on one value discipline, namely Customer Intimacy because customers are the main factor in the success of a bank.